Robotics Current Issues and Trends - Siti Nurmaini (Computer Engineering and Applications Journal, 2013)
The ongoing research and development work in the field of robotics have resulted in so many new technological trends. There are revolution which are being achieved with the use of latest technology in robotics, giving birth to new possibilities for automating tasks and enriching human lives for better. One can easily witness the presence of robotics in every sphere of life from industrial robots, service robots to personal robots. It other words, robots have become a part of our world to meet new demands of a new society.DOI:Â 10.18495/comengapp.21.117120